A Review of the Knops Blood Group System - Xiaohui Ma MD; Zhen Zhao MD; Yan Zhang MD; Lingbo Li MD; Jing Zhong MD (Clinical and Applied Thrombosis/Hemostasis)
The Knops blood group system is an independent blood group system recognized by International Society of Blood Transfusion (ISBT) in 1992, and latest time consisting of 13 antigens carried on a glycoprotein of 2489 amino acids and called the Complement C3b/C4b Receptor 1 (CR1). Erythrocyte KN antigen was first reported in 1970, and CR1 is a protein coding gene that is a member of the receptors of complement activation (RCA) family and is located in the “cluster RCA” region of chromosome 1. CR1 is an important participant in the erythrocyte immune machinery and plays an major role in inhibiting complement activation, and polymorphisms in its expression have been closely associated with a variety of diseases, including systemic lupus erythematosus (SLE), malaria, Plasmodium falciparum malaria, Alzheimer's disease (AD) and leprosy. Antibodies to the Knops system usually do not bind to complement and do not cause a hemolytic reaction. However, anti-Knops antibodies can be detected in the serum of some pregnant women. Generally, however, they only test positive by direct antiglobulin test (DAT) and most of them do not cause hemolytic disease of the newborn (HDN). This article is a review of the progress of the Knops blood group system.